2021
DOI: 10.3390/foods10020263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Active-Edible Coating and Essential Oils on Lamb Patties Oxidation during Display

Abstract: The use of natural products to reduce the use of synthetic additives in meat products, reducing the oxidation and improving the shelf life is a current challenge. Meat quality from lamb patties during 10 days of display on modified atmosphere packaging (MAP) and active-edible coating were tested under six treatments: uncoated patties without coating (CON); patties with alginate coating (EC) and patties with coating and 0.1 or 0.05% of essential oils (EOs) from either thyme (TH 0.1; TH 0.05) or oregano (OR 0.1;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
3
10
0
1
Order By: Relevance
“…Meat coated with edible films containing TEO was kept under modified atmosphere packaging (MAP) for 1, 3, 7, and 10 days at 2 and 4 °C. In comparison to the control meat samples, TEO caused lower values of lipid oxidation, DM losses, and pH, better color (lower lightness but higher redness and yellowness), and increased antioxidant capacity . Similar results with edible films containing TEO were earlier reported by Vital et al and Guerrero et al These results were similar to the results obtained from our study.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Meat coated with edible films containing TEO was kept under modified atmosphere packaging (MAP) for 1, 3, 7, and 10 days at 2 and 4 °C. In comparison to the control meat samples, TEO caused lower values of lipid oxidation, DM losses, and pH, better color (lower lightness but higher redness and yellowness), and increased antioxidant capacity . Similar results with edible films containing TEO were earlier reported by Vital et al and Guerrero et al These results were similar to the results obtained from our study.…”
Section: Resultssupporting
confidence: 92%
“…The changes in color parameters by the days of storage in all treatment groups in our study were found to be similar to the results reported previously, with red meat coating with an edible film containing EO , but a degree of reduction in color parameters, especially in the L * value, which is comparatively low with all EO-treated groups. However, some other studies demonstrated that mixing plant EO with the meat products with or without inoculation of pathogen bacteria or coating meat with edible films containing EO kept all the color parameters almost unaffected or prevented the color losses during storage at 4 °C. ,,,, In these studies, the meat coated with an edible film containing no EO even provided a protection of the meat color. Thus, edible coating films may exhibit a water-barrier property and retain water in the product .…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Several studies on the effect of edible films and coatings on different foods have been carried out (Eom et al., 2018; Eswaranandam et al., 2004; Lin & Krochta, 2005; Ojagh et al., 2010; Pelaes Vital et al., 2021; Vargas et al., 2006), though as far as we know, only one on sushi (Kulawik et al., 2019). A potential polymer for producing bioactive edible coating is chitosan, a cationic byproduct of chitin (Delaviz et al., 2015; Rinaudo, 2006).…”
Section: Introductionmentioning
confidence: 99%